The Republic of Korea : PIM Reform after the Financial Crisis - Hyung-Kim, Jay (World Bank, Washington, DC, 2014)
The financial crisis that hit the Republic of Korea in the second half of 1997 had a devastating impact on its economy, causing the worst recession since the Korean War era. To address the fundamental causes of the crisis and revitalize the economy, the Korean Government took bold, decisive steps to initiate comprehensive structural reforms. The major focus of reform in the fiscal and public sector was to adopt a series of initiatives for strengthening public investment management. The Government endeavored to instill a performance-oriented approach in the system, which implies management of public expenditure based on the principle of value for money. This chapter explains the institutional setting for public investment management (PIM) and the Korean Government s efforts to develop and manage a comprehensive PIM reform to further improve value for the money invested. The Ministry of Strategy and Finance played a leading role by implementing an effective appraisal and evaluation system to tighten the expenditure monitoring of total project cost and introducing a new budgeting system called the Medium Term Expenditure Framework. An initiative of the preliminary feasibility study (PFS), introduced in 1999 and conducted mainly by the public and private Infrastructure Investment Management Center, has been successful in handling the pass-or-fail bottleneck of the whole project selection process. The total project cost management system (TPCM), strengthened after the crisis, is working satisfactorily by discouraging the request frequency and the amount of TPC increases in line ministries. A reassessment study of feasibility is an innovative tool to control and keep the total project cost limit in the middle of TPCM. However, the performance monitoring and evaluation system on PIM still has room for improvement in Korea. A greater emphasis on program evaluation is being called for, with the Government currently establishing a performance-orientation, a greater use of performance contracts can be encouraged.